Effects of antiresorptives and Co-medications on 3D gingival cell Co-cultures - Ekholm-Kerppola, Heidi Maria; Löyttyniemi, Eliisa; Soukka, Tero; Rautava, Jaana (SAGE Publications, 2026)
Introduction
Bisphosphonates and denosumab are the most common antiresorptive drugs (ARs). ARs may cause medication-related osteonecrosis of the jaw (MRONJ) as a side effect, characterized by osteonecrosis and ulceration of the oral mucosa. The pathophysiology of MRONJ remains partly unclear and there is currently no consensus on its multietiological background. Immunomodulatory medications such as corticosteroids and antiestrogens may affect MRONJ onset.
Methods
An in vitro 3D cell culture model of gingival, keratinocytes, and fibroblasts were used to elucidate the pathogenesis of MRONJ. Cell cultures were exposed to ARs, followed by exposures to corticosteroids or antiestrogens. Morphology and proliferation were evaluated.
Results
Among the ARs, alendronate caused the most negative cellular changes, while zoledronate only had a few effects. Denosumab caused more morphological cell atypia and proliferation than other ARs. The combined exposures of individual ARs with corticosteroids had some additional negative effects on gingival cells, whereas ARs with antiestrogen had few effects. The results are partly inconsistent, indicating that 3D cell culture experiments may not be the most suitable method for studying the effects of ARs.
Conclusion
This study suggests that alendronate and denosumab affect gingival cell growth in a 3D cell culture model. These effects are smaller than reported in previous monolayer studies.